Transformações na estrutura produtiva do aglomerado metropolitano de Curitiba - Garcia, Mônika Christina Portella [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
The Metropolitan Accumulation of Curitiba faces a new reality characterized for the insertion to the local economies of great groups in the dynamic sectors, especially to the automobile industry, segment of light vehicles. This process reflects the current phase global of territorial expansion of the capitalist relations, with accented transformation of the innovations social techniques and of production and of the organization modes standards of the local space. The insertion of the Economic Group in a new territory obeys a new organization mode dynamics and of relations where the place also if detaches, constructing strategical agreements that provoke significant changes in the relations between Group and territory. The thematic central office of this work is to understand and to analyze the relation between the sector (automobile - Grupo Renault) and the territory (AMC - Agglomerated Metropolitan of Curitiba), its construction dynamic and crumbling dynamic. A new dynamics of industrial centerless and permanence of the sectors in the place has been broken of the central hypothesis of that the global processes that characterize a new economic phase reflect in the relation between the Economic Groups and the territory, imposing. From this idea it was analyzed influence of the global processes in the organization of the industries, as well as the relations that if process between the Economic Group and the territory, having itself in sight the local dynamics of the auto industries and the competitiveness between the places. Therefore, the characterization of the territorial dynamics of the automobile industry (genesis, determinative and displacements) in the world became excellent, specifying itself the new territories of this sector in Brazil and exposing the logics of localization in the AMC (the new territoriality imposed for the auto industry and its impacts for the local development)... (Abstract complete, click electronic address below).
Keywords: Geografia econômica; Indústria automobilística; Automobile industry; Economic geography